Software-Defined Radio-Based IEEE 802.15.4 SUN FSK Evaluation Platform for Highly Mobile Environments - Jaeseok Lim; Keito Nakura; Shota Mori; Hiroshi Harada (IEEE Open Journal of Vehicular Technology)
IEEE 802.15.4 smart utility network (SUN) frequency-shift keying (FSK) has attracted considerable attention as a wireless communication standard designed for use in essential applications required by Internet of Things (IoT) systems. However, longer transmission distances in highly mobile environments are required to support various applications in next-generation IoT systems, such as vehicle-to-everything, automated driving, and drone control systems. Although research on wide-area, highly mobile communications has been conducted via computer simulations, an experimental evaluation platform for further research has not been developed. In this study, we developed an experimental evaluation platform for SUN FSK in very high frequency bands. The developed platform comprises a signal generator-based transmitter and a software-defined radio-based receiver. It was proven to be capable of transmitting a power of ≥5 W through a power amplifier and was suitable for laboratory and field experiments. In addition, we developed received signal processing methods, including a packet detection method and a channel estimation method, which were designed to achieve wide-area, highly mobile communication. In laboratory experiments, the packet error rate characteristics required by IEEE 802.15.4 were achieved even at a transmission distance of >10 km at vehicular speeds of several tens of km/h.